Odpowiedzi

2009-11-22T15:51:47+01:00
(2x+2y=8
(2x-3y=7

2x=8-2y
2x-3y=7

x=4-y
2(4-y)-3y=7

x=4-y
8-2y-3y=7

x=4-y
-5y=7-8

x=4-y
-5y=-1 /*(-1)

x=4-y
5y=1

x=4-y
y=⅕

x=4-⅕
y=⅕

x=3⅘
y=⅕

------------------
(8x-6y=10
(7x+y=5

y=5-7x
8x-6(5-7x)=10

y=5-7x
8x-30+42x=10

y=5-7x
50x=10+30

y=5-7x
50x=40

y=5-7x
x=⅘

y=5-7*⅘
x=⅘

y=-⅗
x=⅘

-------------------

(4(x-2)-(y-2)=1
(10x-2y=18

4x-8-y+2=1
-2y=18-10x /*(-1)

4x-y=1+6
2y=10x-18

4x-y=7
y=5x-9

4x-(5x-9)=7
y=5x-9

4x-5x+9=7
y=5x-9

-x=7-9
y=5x-9

-x=-2 /*(-1)
y=5x-9

x=2
y=5*2-9

x=2
y=1

-------------------

(2x-4(y+1=10
(2-(x+391-5) sprawdź w ksiażce jak poprawnie wygląda to równanie
obliczę Ci dla:

(2x-4(y+1)=10
(2-(x+391)=5

2x-4y-4=10
393-x=5

2x-4y=14
-x=5-393

-4y=14-2x /*(-1)
-x=-388 /*(-1)


x=388
4y=2x+14

x=388
4y=2*388+14

x=388
4y=790

x=388
y=197,5

2009-11-22T15:52:04+01:00
(2x+2y=8
(2x-3y=7 / *(-1)

2x+2y=8
-2x+3y=-7

5y=1/ :5
y=0,2

2x+2y=8
y=0,2

2x+2*0,2=8
y=0,2

2x+0,4=8
y=0,2

2x=8-0,4
y=0,2

2x=7,6/:2
y=0,2

x=3,8
y=0,2

••••••••••••••
(8x-6y=10
(7x+y=5/*6

8x-6y=10
42x+6y=30

50x=40/:50
x=0,8

8x-6y=10
x=0,8

8*0,8-6y=10
x=0,8

6,4-6y=10
x=0,8

-6y=10-6,4
x=0,8

-6y=3,6/:(-6)
x=0,8

y= -0,6
x=0,8